(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objectives: This study aims to investigate the impact of breakfast skipping on the risk of developing Type 2 Diabetes Mellitus among university students in Karachi, Pakistan. Background: In recent years, several studies have suggested a strong link between skipping breakfast and an increased risk of obesity, overweight, and subsequently Type 2 Diabetes Mellitus. Skipping breakfast may lead to poor metabolic regulation, higher body mass index (BMI), and insulin resistance, which are significant risk factors for diabetes. Understanding these patterns among young adults is crucial for implementing effective health-promoting interventions. This study builds upon previous research by examining the behavior and consequences of breakfast skipping in a university student population. Study Design: Cross-Sectional Study Study Setting: It was Conducted at the Department of Community Health Sciences of Bahria University of Health Sciences, Karachi. Study Duration: November 2022 – April 2023 Methodology: A sample size of 384 was calculated using Epi-info, with a 95% confidence interval and a 5% margin of error. A random sampling method was employed. Data were analyzed using IBM SPSS Statistics 23. Linear regression was applied to assess the association between breakfast skipping and the risk of developing Type 2 Diabetes. A p-value of <0.05 was considered statistically significant. Results: Out of 383 participants, 144 (36.5%) were identified as breakfast skippers, while 63.5% reported regularly consuming breakfast. The primary reason cited for skipping breakfast was lack of time (59%). The most represented age group was 20 years (24.6%), and females comprised the majority of participants (58.9%). Most students acknowledged that eating breakfast enhances energy levels and cognitive performance, although approximately 40% remained neutral, and less than 10% disagreed. Conclusion: The results showed no significant association between breakfast skipping and the risk of developing Type 2 Diabetes Mellitus among the students. Thus, the null hypothesis was accepted, indicating no direct link between breakfast habits and diabetes in this population.